Selenium-Biofortified Alfalfa Hay Supplemented to Jersey and Holstein Dairy Heifers During the Peripartum Period: Effects on Dams and Their Offspring - Shana Jaaf; Matteo Mezzetti; Sebastiano Busato; Erminio Trevisi; Massimo Bionaz (Animals, 2025)
The objective of the study was to assess whether supplementing dairy heifers with Se-biofortified hay during the last 40 days of pregnancy and early lactation improves performance, metabolism, oxidative status, and immune response in the dams and their calves. Ten Jersey and eight Holstein pregnant dairy heifers were divided into two groups and supplemented with Se-biofortified or a control alfalfa hay from 40 days before to 2 weeks postpartum. The calves born to the heifers were also monitored during the first month of life. Supplementation of Se-biofortified hay improved milk yield in Holstein heifers only, but had minor effects on blood parameters measured and the liver transcriptome. Similarly, we did not detect any impact of feeding Se-biofortified hay to heifers on their offspring. The data indicated a better immune system and oxidative status in Holstein compared to Jersey heifers. Overall, our data did not support the hypothesis that supplementing Se-biofortified hay to pregnant heifers improves their performance and the health of dams and offspring, at least at the dose we provided.